VD_FINDINFO Décision / 2011 / 689 vom 23. November 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE | 147 CPP (CH), 221 al. 1 let. c CPP (CH), 221 al. 2 CPP (CH), 221 CPP (CH), 226 CPP (CH)